2014
DOI: 10.1212/wnl.0000000000000842
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of dementia in Parkinson disease

Abstract: Cardiovascular autonomic dysfunction, REM sleep behavior disorder, color discrimination ability, and gait dysfunction strongly predict development of dementia in Parkinson disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
259
7
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 345 publications
(298 citation statements)
references
References 42 publications
(41 reference statements)
19
259
7
1
Order By: Relevance
“…Since PD patients with RBD are likely to develop dementia and hallucinations (Anang, et al, 2014,Sinforiani, et al, 2008, eventually presenting a phenotype similar to DLB, and based on the current and previous genetic and post-mortem results , we hypothesize that RBD-associated synucleinopathy (the central common area in Figure 1) is the same clinicalpathological entity, whether it is defined as parkinsonism first with subsequent dementia and hallucinations, or whether it is defined as DLB with subsequent parkinsonism. In that sense, RBD can be considered as a marker for diffuse synucleinopathy, which may be a better description of the disease than DLB or PD with dementia.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Since PD patients with RBD are likely to develop dementia and hallucinations (Anang, et al, 2014,Sinforiani, et al, 2008, eventually presenting a phenotype similar to DLB, and based on the current and previous genetic and post-mortem results , we hypothesize that RBD-associated synucleinopathy (the central common area in Figure 1) is the same clinicalpathological entity, whether it is defined as parkinsonism first with subsequent dementia and hallucinations, or whether it is defined as DLB with subsequent parkinsonism. In that sense, RBD can be considered as a marker for diffuse synucleinopathy, which may be a better description of the disease than DLB or PD with dementia.…”
Section: Discussionmentioning
confidence: 92%
“…With long term follow-up, more than 80% of individuals with idiopathic RBD developed either Parkinson's disease (PD), dementia with Lewy bodies (DLB) or multiple system atrophy (MSA) ,Schenck, et al, 2013. It was suggested that RBD may define a subtype of PD patients (Fereshtehnejad, et al, 2015,Gagnon, et al, 2004 with cognitive decline (Gagnon, et al, 2009,Vendette, et al, 2007, dementia (Anang, et al, 2014), hallucinations (Sixel-Doring, et al, 2011) and autonomic dysfunction (Postuma, et al, 2008), as compared to PD patients without RBD. In addition, pathological studies in brains of PD patients with and without RBD demonstrated a more widespread -synuclein accumulation in those associated with RBD .…”
Section: Introductionmentioning
confidence: 99%
“…The pattern of cognitive deficits in PDD and DLB, however, appears to differ in significant ways from that of AD [4-7, 9, 10, 23]. Furthermore, evidence suggests that there are specific relationships between motor and gait impairment patterns and the type of cognitive impairment or dementia condition present [1,2,[24][25][26][27][28][29][30].…”
Section: Dw Scharre Et Al / Comparing Lbd With Ad and Pdmentioning
confidence: 99%
“…Research on the diagnosis and management of dementia with Lewy bodies (DLB) has increased greatly in the past decade [1][2][3][4][5][6][7][8][9][10][11]. Currently it is thought that DLB represents about 10-15% of all dementia cases [12].…”
Section: Introductionmentioning
confidence: 99%
“…Demographic features such as the subject's age, age at onset of motor symptoms, and disease duration are significant predictors of cognitive impairment in PD [18] [19] [20]. Several NMS, including neuropsychiatric (depression, hallucinations) and sleep disorders (REM sleep behavior disorder, RBD) [21] and cardiovascular autonomic failure [22] are positively associated with the development of dementia in PD. As to the motor features, cognitive deficit is significantly more frequent and severe in akinetic-rigid in comparison to tremor-predominant cases of PD [23].…”
Section: Cognitive Impairment In Pdmentioning
confidence: 99%